WRITING TEACHING STRATEGIES IN ONLINE LEARNING BY JUNIOR HIGH SCHOOL ENGLISH TEACHER - Ana Hasibuan; Maylin Gita Monika Ginting (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2022)
Abstract A strategy is a tool that helps teachers in learning at school face-to-face or online. A strategy is needed so that teachers can see a picture of what learning was to be achieved, what will be done during education, and what should not be done. In online learning, teachers must be able to apply appropriate strategies in teaching and improve students' writing skills. The research method used in this research is a descriptive qualitative method through surveys using questionnaires or google forms distributed to 10 English teachers who teach in junior high schools. There are three stages of learning carried out by the teacher, namely preparation of learning, the practice of learning, and evaluation of learning. The preparation made by the teacher is to prepare learning materials and media. In practice, teachers use learning strategies such as Quick Writers, Visualization, Brainstorming, and Journaling. And the methods used are Free Writing, Journalistic, Cluster Mapping, and Brainstorming. And the evaluation writing teacher always evaluates student writing.